Coptis alkaloids improve gluconeogenesis and lipid accumulation in mouse primary hepatocytes - YAN Jiaqi, WANG Siqi, WANG Zheng, LI Jun (Jichu yixue yu linchuang, 2023)
Objective To screen the alkaloid monomer of coptis chinensis, which can improve the gluconeogenesis and lipid accumulation of mouse primary hepatocytes, and to explore its mechanism.Methods The mouse primary hepatocytes were isolated and incubated with different doses of coptis alkaloids and coptis chinensis monomer. The cell viability was measured by CCK-8 method. Sodium pyruvate, sodium lactate and glucagon were added to induce the gluconeogenesis model of mouse primary hepatocytes. The content of glucose in the medium was detected by the kit. The expression of gluconeogenesis-related genes was detected by RT-qPCR. The protein p-AKT was detected by Western blot. Palmitic acid and oleic acid were used to induce lipid accumulation model. The lipid content was detected by oil red O staining. The protein level of FAS, PLIN1 and PPARγ was detected by Western blot. Results The cell viability of mouse primary hepatocytes was more than 80% after 24 h treatment with low dose of coptis alkaloids (0.5, 1, 2 μg/mL). Content of glucose and mRNA of G6PC and PCX in gluconeogenesis model group were higher than that in control group (P＜0.05), while p-AKT protein level was lower than that in control group(P＜0.05). Compared with model group, the glucose content and the mRNA levels of G6PC and PCX were lower in that treated with coptis alkaloids (1, 2 μg/mL) and berberine (2.5, 5 μmol/L) (P＜0.05), while the protein level of p-AKT was higher (P＜0.05). Oil red O staining in the lipid accumulation model group increased compared with that in the control group (P＜0.01), and the protein level of FAS, PLIN1, PPARγ was higher than that of the control group (P＜0.01).Oil red O staining of groups that treated with coptis alkaloids (1, 2 μg/mL), coptisine (2.5, 5 μmol/L) and berberine (2.5, 5 μmol/L) were less than that of model group (P＜0.05), and the protein level of FAS, PLIN1, PPARγ was lower than that of the model group (P＜0.05). Conclusions Berberine decreases the gluconeogenesis of mouse primary hepatocytes through p-AKT pathway. Coptisine and berberine reduce the expression of FAS, PLIN1, PPARγ and decrease the accumulation of lipid in mouse primary hepatocytes.